Mast cell degranulation inhibits motor patterns of human ileum and sigmoid colon in vitro: relevance for postoperative ileus. Issue 8 (13th May 2015) - Rychter, J.; Ortega, O.; Berdun, S.; Arenas, C.; Lopez, I.; Espin, F.; Vergara, P.; Clavé, P.
Abstract Background Local release of mast cell proteases during gastrointestinal surgery is associated with the inhibition of motility and postoperative ileus (POI). We determined whether activation of intramuscular mast cell affects the motor patterns of the human ileum and colon and whether proteases are involved. Methods Motor response of ileal and colonic circular muscle strips was measured in organ bath. Mast cell degranulation was induced by compound 48/80 (c48/80; 25–675 μg/mL). Motor response was quantified as tone, rhythmic phasic contractions (RPCs) and contractions to electric field stimulation (EFS; 40 Hz), and bethanechol‐evoked contractions. Ketotifen (10−6 mol/L) and a protease inhibitor cocktail (P8340) were used to evaluate the role of mast cell mediators. Key Results (a) c48/80 impaired the spontaneous and the electrically evoked motor response in small bowel and colonic strips (sigmoid colon EC50: 460.0 μg/mL for RPCs and 8.9 μg/mL for electrically evoked contraction amplitudes) and bethanechol‐evoked contractions. (b) Preincubation with ketotifen (10−6 mol/L, 1 h) prevented the impairment of RPCs and EFS‐evoked contractions in the sigmoid colon and ileum but not in the right colon. (c) Preincubation with P8340 also prevented the impairment of contractions in the sigmoid colon but not in the ileum or the right colon. Conclusions & Inferences Mast cell degranulation by c48/80 inhibits the spontaneous and the nerve‐mediated motor response in the human ileum and colon. The effect is partially mediated by mast cell proteases and could be relevant in the pathophysiology of POI.